Validity of guided inquiry-based modules on digestive system to improve argumentation skill - Hendarto, Puji; Maridi, M.; Prayitno, Baskoro Adi (Jurnal Pendidikan Biologi Indonesia, 2019)
Students tend to be passive in learning activities if the media is less supportive. Module development as a learning medium can overcome the passivity of students. The purpose of this research was to determine the validity and feasibility of the guided inquiry-based module on Human Digestive System materials to improve students' argumentation skill. This research is Research and Development. The research was conducted at class VIII of State Junior High School 3 of Surakarta. The module comprised of into three parts, namely the introduction, content, and closing. The contents section consisted of three sub-materials, namely: 1) food substances; 2) food digestion organs and processes; and 3) food digestive system disorders. The module feasibility was tested through the assessments of media, subject matter, learning experts and linguists. The results of experts’ evaluation toward the module showed that the module was feasible with the percentages were 88.28% (media design), 90.125% (material), 91.15% (learning aspect), and 94.8% (language). Therefore, the module is feasible to be used as a learning medium to improve students' argumentation skill.